Critical fators to Quality Management System implementation: Relevant literature review 1992-2012 - Almeida, Diogo [UNESP]; Muniz, Jorge [UNESP]; Costa, Antionio Fernando Branco [UNESP] (My University, 2014)
The Quality Management System supports stable processes and their better management. Sustainable implementation and maintenance are influenced by some factors. This paper presents critical factors to Quality Management System implementation. The ISO 9001 is the most popular QMS around the world wide organizations. They are identified from literature review (1992-2012). 51 papers were analyzed and 10 critical factors were identified: top management commitment, team commitment, training for the team involved, defined responsibilities and authorities between the team involved, schedule for implementation, Quality oriented culture in the organization, resource allocation, integration between the areas involved, management system without bureaucracy and awareness of the people about the importance of ISO 9001.
Keywords: Critical factors; Implementation; ISO 9001; Quality Management System